HUBUNGAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PENDIDIKAN KEWARAGANEGARAAN - Nurdin Nurdin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: This study aims to determine how much the motivation have a relationship with school performance in middle school civic education di SMP Pabuaran Bogor. The research was conducted in the school year 2013 - 2014 for the first semester . The population was eighth grade students as much as 8 classes totaling 320 students . Samples were taken 64 students citizenship randomly selected . The results of the data processing , the value of t = 7.933 > = 1.670 .at table value at 5 % means the students' motivation have a relationship with civic education learning achievement . The coefficient of determination ( R2 ) of 0.504 means 50.4 % have a relationship student motivation and the learning achievement of civic education , while the remaining 49.6 % ( 100 % - 50.4 % ) affected by other factors that were not analyzed in this study . Keywords : student motivation; learning achievement